Native soil: contest and control for land and resource rights in the Arctic - Hodgson, Kara, author; Betsill, Michele, advisor; Velasco, Marcela, advisor; Schultz, Courtney, committee member (Colorado State University. Libraries, 2019)
The Arctic is a dynamic region that over four million people in eight different countries call their home. Many of the residents belong to indigenous groups who have lived there for millennia. These groups have retained their traditional cultural practices, values, and livelihoods while also having had to adapt to contemporary realities. Since the mid-twentieth century, the region has been increasingly seen as an appealing option for the exploitation of vital natural resources. As such, there has been contestation between industrial actors and Arctic indigenous groups over control of the land and its resources. States have played a pivotal role in mediating the tensions arising from interests in extractive industry development and indigenous groups' rights. In each of the cases presented in this paper, the states have chosen to incorporate their indigenous populations as the solution, although each has done so in a decidedly different way. This paper traces the ways in which indigenous peoples have been incorporated and how their rights to their ancestral lands have been recognized in three different Arctic countries, particularly in situations where there are conflicting interests over the land usage. It posits that the unique historical evolution of institutions in each country, with their idiosyncratic path dependencies and critical junctures, explains why they, and why countries in general, vary in the methods of incorporation they choose.
Keywords: critical junctures; path dependence; incorporation; land rights; Indigenous peoples; Arctic